Climate induced variation in forest fire using Remote Sensing and GIS in Bilaspur District of Himachal Pradesh (International Journal of Engineering and Computer Science, 2017)
Himachal Pradesh forests have frequent incidents of forest fires especially in the months of March to June which causes loss of forest wealth, biodiversity, ecology and environment. Due to the scarcity of a broad and efficient work to be acquainted with its fire-sensitive forest regions. Hence, the current study was carried out in Bilaspur district of Indian Western Himalaya to identify forest fire by overlaying geographical coordinates of weighted thematic layers such as elevation, slope, aspect, mean annual temperature, humidity, wind speed, accessibility to habitation & settlement and fuel map of the region. In the present study Climate induced variation in forest fire in Bilaspur District of Himachal Pradesh were estimated. The LISS 3 and ASTER DEM has been used for forest fire risk map, Forest density map, land use /land cover ,extraction of DEM features and other spatial object in which the topography of the area represents the forest type and various land forms of the study area. The fire-sensitive regions were further prioritized into very high, high, medium, low, and very low forest fire-prone areas. The Pinus roxburghii forest type, low elevation, high temperature, high slope, south-west facing aspect, May month and anthropogenic disturbances were identified as major factors responsible for forest fire in the region. The half of the forest cover was identified as fire sensitive.